![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(35-3.\left|x\right|=5.\left(2^3-4\right)\)
\(35-3.\left|x\right|=5.\left(8-4\right)\)
\(35-3.\left|x\right|=5-4\)
\(35-3.\left|x\right|=1\)
\(3.\left|x\right|=35-1\)
\(3.\left|x\right|=34\)
\(\left|x\right|=34:3\)
\(\left|x\right|=\frac{34}{3}\)
\(=>x=\frac{34}{3}\)hoặc \(x=-\frac{34}{3}\)
b)\(10+2.\left|x\right|=2.\left(3^2-1\right)\)
\(10+2.\left|x\right|=2.\left(9-1\right)\)
\(10+2.\left|x\right|=2.8\)
\(10+2.\left|x\right|=16\)
\(2.\left|x\right|=16-10\)
\(2.\left|x\right|=6\)
\(\left|x\right|=6:2\)
\(\left|x\right|=3\)
\(=>x=3\)hoặc \(x=-3\)
a)35-3|x|=5(8-4)
35-3|x|=5.4=20
3|x|=35-20=15
|x|=15:3=5
=>x=5 hoặc x=-5
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\frac{3}{35}-\left[\frac{3}{5}+x\right]=\frac{2}{7}\)
\(\Rightarrow\frac{3}{5}+x=\frac{3}{35}-\frac{2}{7}\)
\(\Rightarrow\frac{3}{5}+x=\frac{3}{35}-\frac{2\cdot5}{35}\)
\(\Rightarrow\frac{3}{5}+x=\frac{3}{35}-\frac{10}{35}=\frac{-7}{35}\)
\(\Rightarrow x=\frac{-7}{35}-\frac{3}{5}=\frac{-7}{35}-\frac{3\cdot7}{35}=\frac{-7}{35}-\frac{21}{35}=\frac{-28}{35}=\frac{-4}{5}\)
\(b,\frac{5}{6}+\frac{1}{6}:x=\frac{3}{4}\)
\(\Rightarrow\frac{1}{6}:x=\frac{3}{4}-\frac{5}{6}\)
\(\Rightarrow\frac{1}{6}:x=\frac{18}{24}-\frac{20}{24}\)
\(\Rightarrow\frac{1}{6}:x=\frac{-2}{24}\)
\(\Rightarrow x=\frac{1}{6}:\frac{-2}{24}=\frac{1}{6}:\frac{-1}{12}=\frac{12}{-6}=\frac{-12}{6}=-2\)
\(c,\left|x-3\frac{4}{7}\right|=-0,5\)
Vì \(\left|x-3\frac{4}{7}\right|\ge0\)mà \(-0,5< 0\)nên \(x\in\varnothing\)
Vậy không có giá trị x thỏa mãn
a) 3/35-(3/5+x)=2/7
<=> 3/5+x=3/35-2/7
<=> 3/5+x=3/35-10/35
<=> 3/5+x=-7/35
<=> 3/5+x=-1/5
<=> x=-1/5-3/5
<=> x=-4/5
Vậy x=-4/5
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 7,24 x X + 2,76 x X = 35
(7,24 + 2,76) x X = 35
10 x X = 35
X = 35 : 10
X = 3,5
b) \(\frac{3}{4}\) - \(\left(x+\frac{1}{7}\right)\) = 6 - \(\frac{11}{2}\)
\(\frac{3}{4}\) - X + \(\frac{1}{7}\) = \(\frac{1}{2}\)
\(\frac{3}{4}\) - X = \(\frac{1}{2}\) - \(\frac{1}{7}\)
\(\frac{3}{4}\) - X = \(\frac{5}{14}\)
X = \(\frac{3}{4}\) - \(\frac{5}{14}\)
X = \(\frac{11}{28}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a.
$(1-\frac{1}{2})(1-\frac{1}{3})(1-\frac{1}{4})....(1-\frac{1}{2011})$
$=\frac{1}{2}.\frac{2}{3}.\frac{3}{4}...\frac{2010}{2011}$
$=\frac{1.2.3...2010}{2.3.4...2011}$
$=\frac{1}{2011}$
b.
$a=35:(3+4)\times 3=15$
$b=35-15=20$
![](https://rs.olm.vn/images/avt/0.png?1311)
a. (5.x + 3) : 4 – 16 = 6
(5.x + 3) : 4 = 22
(5.x + 3) = 88
5.x = 85
x = 13
b. 7(23 – 3.x) : 2 – 35 = 35
7(23 – 3.x) : 2 = 70
7(23 – 3.x) = 35
7 . 3.x = 12
7.x = 4
x = 4/7
a.) (5.x + 3) : 4 – 16 = 6
=> (5.x + 3) : 4 = 22
=> 5.x + 3 = 88
=> 5x = 85
=> x = 17
b) 7(23 – 3.x) : 2 – 35 = 35
=> 7(23 – 3.x) : 2 = 70
=>7(23 – 3.x) = 140
=> 23 – 3.x = 20
=> 3x = 3
=> x = 1
\(35-|x-1|=3^2-4=9-4=5\Rightarrow|x-1|=35-5=30;\)
\(\left(+\right)x-1=-30\Rightarrow x=-30+1=-29\)
\(\left(+\right)x-1=30\Rightarrow x=30+1=31\)